Insights into the venomology of the Red Sea lionfish (Pterois miles, Scorpaenidae): venom protein identification and anti-cancer efficacy - Khalil, May Y. (AUC Knowledge Fountain, 2013)
The common lionfish, Pterois miles (Scorpaenidae), is one of the most abundant and venomous fishes that inhabit the Egyptian Red Sea. This research for the first time identifies the venom protein of Pterois miles and shedds light on its toxic capabilities. Different biochemical techniques were used to investigate the identity of the venom protein including: SDS-PAGE, Size Exclusion Chromatography (SEC) and Mass Spectrometry. Crude protein homogenates were compared between the venomous dorsal spines and the non-venomous caudal fin (tail). Anti-cancer efficacy of the isolated venom protein was also investigated using cell culture of the HepG2 cancer cell lines, coupled to in vitro MTT cytotoxicity assays. A 75 kDa protein band, present only in the venomous spine crude homogenate, and absent in the tail, revealed strong molecular weight similarity to the venom protein of the sister lionfish species, Pterois volitans. The crude venomous spine homogenate also showed an anti-cancer effect on the HepG2 cell lines at very low concentrations, which was absent in the tail crude homogenate. Furthermore, upon SEC fractionation only those fractions containing the purported venom protein band demonstrated cytotoxic effects on HepG2 cancer cell lines. These findings suggest further investigations into the anti-cancer efficacy of the venom protein of Pterois miles has great potential for biotechnological advances in tumor research.